Working at warp speed : the new rules for project success in a sped-up world - Flicker, Barry, 1949- (Berrett-Koehler Publishers, 2002)
Everyone is a project manager-projects are what all of us do day in and day out. Skillful project management is fundamental to survival in today's warp-speed world. Yet it is often misunderstood, leading to unrealistic deadlines, poorly defined goals, and wasted time. The secret to successful project management, argues Barry Flicker, is making and keeping clear commitments-far easier said than done in a time of complex, cross-departmental projects and sometimes unclear lines of authority. Through a story about people confronting daily frustrations on the job, Flicker demonstrates how shifting.